The prospective acceptability of preventative IV bisphosphonate therapy prior to fracture: Perspectives of young people with Duchenne muscular dystrophy, parents and health professionals - Danielle C. Mountain; Nicola Crabtree; Claire L. Wood; Sze Choong Wong; Lucy Bray (PLoS ONE, 2025)
Young people with Duchenne muscular dystrophy (DMD) commonly experience osteoporosis and fractures which can lead to chronic pain and reduced quality of life. Initiating IV bisphosphonate therapy prior to first fracture may be a logical primary preventative approach given the extent and related morbidity of osteoporosis, although there is limited evidence for this. This qualitative study using semi-structured interviews and focus groups, aimed to explore the opinions and prospective acceptability of young people with DMD, parents and health professionals in the UK on initiating bisphosphonate therapy prior to first fracture. Four boys with DMD (aged 15–17 years) and 20 parents participated in semi-structured interviews. Twenty-seven health professionals involved in the care of young people with DMD participated in focus groups. A framework analysis was conducted. Three categories were identified which represented a continuum of opinions on the endorsement of preventative bisphosphonate therapy: 1) “It buys them time”, endorsement of preventative bisphosphonate therapy; 2) Uncertainty and the importance of “choice”; and 3) “Worry about... starting bisphosphonates even earlier”, not endorsing the use of preventative bisphosphonate therapy. Young people with DMD and parents discussed a range of opinions about the prospective acceptability of IV bisphosphonate as preventative therapy, highlighting the importance of family choice before initiation of therapy. Health professionals called for future research exploring the risks and benefits of preventative IV bisphosphonate therapy for young people with DMD to inform clinical practice.